2015
DOI: 10.1097/fch.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Youths As Partners in a Community Participatory Project for Substance Use Prevention

Abstract: This community-based participatory research project aimed to develop strategies to prevent youth substance use in a rural county. This article (1) describes the project phases, (2) examines unique contributions and considerations of youth involvement, and (3) explores the youths' perspective. Twelve youths, aged 16 to 18 years, joined parents, community leaders, and research specialists on the community-based participatory research team. The youths were integrally involved in all phases including the community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…In eight of the 14 studies, a researcher associated with a university served as one of the adult facilitators. Several studies suggested that youth researchers improved the recruitment and engagement of research participants (Gomez & Ryan, ; Kulbok et al., ; Walker & Saito, ). Youth knew where other youth spent their time, particularly youth who were hard to reach or were not involved in traditional programs; thus, researchers’ gained access to populations typically underrepresented in empirical studies (Walker & Saito, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In eight of the 14 studies, a researcher associated with a university served as one of the adult facilitators. Several studies suggested that youth researchers improved the recruitment and engagement of research participants (Gomez & Ryan, ; Kulbok et al., ; Walker & Saito, ). Youth knew where other youth spent their time, particularly youth who were hard to reach or were not involved in traditional programs; thus, researchers’ gained access to populations typically underrepresented in empirical studies (Walker & Saito, ).…”
Section: Resultsmentioning
confidence: 99%
“…Youth knew where other youth spent their time, particularly youth who were hard to reach or were not involved in traditional programs; thus, researchers’ gained access to populations typically underrepresented in empirical studies (Walker & Saito, ). Young people built rapport with their peers (Kulbok et al., ) and helped young people overcome hesitations to participate in research, as they were not viewed as authority figures (Gomez & Ryan, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the development of individual action, increases in competencies for action and research were referred [34,35] in study 1, and the development of interpersonal skills through dealing with people with different personalities, and self-confidence [36] were identified in study 2. The increased political capacity converges in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…One of the peer leaders' main roles was as research partner in the community assessment (see Kulbok et al, 2015, andLincoln, Borg, &Delman, 2015, for examples of youth researchers in health promotion). The peer leaders were responsible for the following:…”
Section: Readying the Hope Peer Leaders And Adultsmentioning
confidence: 99%